2016
DOI: 10.1051/0004-6361/201527760
|View full text |Cite
|
Sign up to set email alerts
|

Probing the clumping structure of giant molecular clouds through the spectrum, polarisation and morphology of X-ray reflection nebulae

Abstract: We introduce a new method for probing global properties of clump populations in giant molecular clouds (GMCs) in the case where these act as X-ray reflection nebulae (XRNe), based on the study of the clumping's overall effect on the reflected X-ray signal, in particular on the Fe K-α line's shoulder. We consider the particular case of Sgr B2, one of the brightest and most massive XRN in the Galactic center (GC) region. We parametrise the gas distribution inside the cloud using a simple clumping model with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The ionizations induced by X-rays that are absorbed in a molecular cloud can strongly affect the chemical balance of the cloud by heating it and increasing the electron fraction (Lepp & McCray 1983;Maloney et al 1996). The sources of X-rays, especially non-thermal sources laro et al 2016;Walls et al 2016;Molaro et al 2016) and shown to be a powerful diagnostic of the incident X-ray flux on a cloud. The inferred luminosity is still far below the Eddington luminosity for Sgr A * , but is 10 4 times brighter than its current luminosity in X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…The ionizations induced by X-rays that are absorbed in a molecular cloud can strongly affect the chemical balance of the cloud by heating it and increasing the electron fraction (Lepp & McCray 1983;Maloney et al 1996). The sources of X-rays, especially non-thermal sources laro et al 2016;Walls et al 2016;Molaro et al 2016) and shown to be a powerful diagnostic of the incident X-ray flux on a cloud. The inferred luminosity is still far below the Eddington luminosity for Sgr A * , but is 10 4 times brighter than its current luminosity in X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…Their work concentrated more on the reflection morphology, while we concentrate on the spectral features and produce the Xspec table model to allow for fitting to real observational data. There is also the work by Molaro et al (2016) which concentrated on the effects of clumpiness in the cloud rather than on the spectral features. This paper is organised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reconstruction of Sgr A*'s past activity record (e.g. [115,116]), one could use the same data as a sensitive and bias-free diagnostic tool for the illuminated gas [117][118][119]. Thanks to the X-ray reflection, eventually we will be able to map the 3D density (and potentially velocity) field of the dense gas inside the inner few hundred parsecs of our Galaxy [120][121][122] and possibly some other nearby galaxies (e.g.…”
Section: Sgr A* and The Galactic Centrementioning
confidence: 99%